Origin of spin incommensurability in hole-doped S=1 Y2-xCaxBaNiO5 chains - Malvezzi, André Luiz [UNESP]; Dagotto, E. [UNESP] (American Physical Soc, 2001)
Spin incommensurability (IC) has been recently experimentally discovered in the hole-doped Ni-oxide chain compound Y2-xCaxBaNiO5 [G. Xu et al., Science 289, 419 (2000)]. Here a two orbital model for this material is studied using computational techniques. Spin IC is observed in a wide range of densities and couplings. The phenomenon originates in antiferromagnetic correlations across holes dynamically generated to improve hole movement, as it occurs in the one-dimensional Hubbard model and in recent studies of the two-dimensional extended t-J model. The close proximity of ferromagnetic and phase-separated states in parameter space is also discussed.
Keywords: Neutron scattering; Phase separation; Semiconductor; Spin trapping; Technique